Supply Chain Management for Servitized Products: A multi-industry case study - Johnson, Mark; Mena, Carlos (Elsevier Science B.V., Amsterdam., 2008)
Manufacturers are combining products and services in order to provide greater value to the customer and to facilitate longer more profitable business relationships. Organisations that pursue this route are following a strategy of servitization which requires the effective management of supply chains. A framework was developed from the extant literature that was used as a lens for the analysis of supply chains for servitized products. This research uses case studies to explore the challenges and opportunities that face the supply chain management function within organisations that are pursuing a strategy of servitization. The case studies indicate that servitized supply chains are different to their production counterparts and need to be responsive which is facilitated by real-time information.
Keywords: Supply chain; Products; Services; Servitisation; Case study